Raise endurance for Ironman 70.3 - Sultana, F. (2018)
Triathlon is an endurance sport. The development of this ability is an essential goal of triathlon training. It`s about becoming able to withstand fatigue in a long-lasting ordeal. The triathlete needs to develop his endurance at the right level and devote himself to it wisely. So what volume and how to go for a Half Ironman?